Impaired mucosal IgA response in patients with severe COVID-19 - Melyssa Yaugel-Novoa; Blandine Noailly; Fabienne Jospin; Andrés Pizzorno; Aurélien Traversier; Bruno Pozzetto; Louis Waeckel; Stéphanie Longet; Sylvie Pillet; Elisabeth Botelho-Nevers; Manuel Rosa-Calatrava; Thomas Bourlet; et al. (Emerging Microbes and Infections)
Several studies have investigated the antibody response to SARS-CoV-2, focusing particularly on the systemic humoral immune response and the production of immunoglobulin G (IgG) antibodies. IgA antibodies play a crucial role in protecting against respiratory viral infections but have also been associated with the pathophysiology of COVID-19. We performed a prospective study of 169 COVID-19 patients – 50 with critical/severe (ICU), 47 with moderate (Non-ICU), and 72 with asymptomatic COVID-19 – to explore the humoral immune response to SARS-CoV-2 infection. We found that the early systemic IgA response strongly induced in patients with severe disease did not block IgG neutralization functions and activated FcRs more effectively than IgG. However, even if SIgA levels were high, mucosal IgA antibodies could not control the infection effectively in patients with severe disease. Our findings highlight the complexity of the immune response to SARS-CoV-2 exhibiting high systemic levels of IgA with strong neutralizing capacity in severe cases, together with higher levels of IgA-FcR activation than in asymptomatic patients. They also suggest the need for further research to fully understand the role of IgA and its structural alterations in mucosal tissues in cases of severe disease and the impact of these antibodies on disease progression.